Tuhan dan Kebudayaan Sebagai Pilar Kehidupan Multikultural - Asmalia, Asmalia; Albina, Meyniar (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study explores the relationship between the concept of God and culture as a foundation for harmonious multicultural life. The background focuses on globalization challenges threatening cultural identity and the importance of divine values in uniting diversity. Employing descriptive qualitative methods with a literature study approach, the research examines scholarly literature to identify patterns of the religion-culture nexus in pluralistic societies. Findings reveal that divine values, such as justice and compassion, serve as the basis for universal morality, while culture acts as a medium to align religious values with social life. In conclusion, the synergy between divine values and culture fosters constructive dialogue, tolerance, and social cohesion in multicultural communities. This article offers both theoretical insights and practical implications for further development